Cover Feature: Star‐Shaped Push‐Pull Molecules with a Varied Number of Peripheral Acceptors: An Insight into Their Optoelectronic Features (ChemPhotoChem 6/2018). Issue 6 (7th June 2018) - Klikar, Milan; Seintis, Kostas; Polyzos, Ioannis; Pytela, Oldřich; Mikysek, Tomáš; Almonasy, Numan; Fakis, Mihalis; Bureš, Filip
Abstract : The Cover Feature illustrates the impact of chromophore arrangement on the fundamental (non)linear optical properties of different star‐shaped push‐pull molecules. The "push‐pull man" is assembled from specific chromophore branches, electron donors and acceptors, and the π‐system. More information can be found in the Article by M. Klikar et al. onpage 465 in Issue 6, 2018 (DOI:10.1002/cptc.201800051 ).